The Relationship Between Reproductive Health Literacy and Risky Sexual Behavior Among Adolescents in Gedog Kulon Village, Turen District, Malang Regency - Amelia Putri Cahyono; Heny Astutik; Retno Dumilah; Ibnu Fajar (Gayaku Publisher, 2026)
Background : Risky sexual behavior among adolescents remains a significant public health issue that can lead to various adverse consequences, including unintended pregnancy, sexually transmitted infections (STIs), and psychological as well as social problems. Low reproductive health literacy is considered one of the factors influencing risky sexual behavior among adolescents. Method : This study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 131 adolescents in Gedog Kulon Village, Turen District, Malang Regency, selected using proportional random sampling. The research instruments were the Health Literacy Measure for Adolescents (HELMA) questionnaire and the Risky Sexual Behavior Index. Data were analyzed using the Spearman Rank correlation test. Result : The results showed that 74% of the respondents had a high level of reproductive health literacy, while 64.1% were categorized as having no risky sexual behavior. Statistical analysis revealed a p-value of 0.002 (<0.05) and a correlation coefficient of r = -0.269, indicating a statistically significant negative relationship between reproductive health literacy and risky sexual behavior. Conclusion : Lower levels of reproductive health literacy may reduce adolescents' ability to make appropriate decisions regarding their sexual behavior. Therefore, improving reproductive health literacy is expected to contribute to the prevention of risky sexual behavior among adolescents